Cross‐country comparison of proportion of alcohol consumed in harmful drinking occasions using the International Alcohol Control Study. (14th February 2018) - Viet Cuong, Pham; Casswell, Sally; Parker, Karl; Callinan, Sarah; Chaiyasong, Surasak; Kazantseva, Elena; Meier, Petra; MacKintosh, Anne‐Marie; Piazza, Marina; Gray‐Phillip, Gaile; Parry, Charles D. H.
Abstract: Introduction and Aims: This study examines the proportion of alcohol markets consumed in harmful drinking occasions in a range of high‐, middle‐income countries and assesses the implications of these findings for conflict of interest between alcohol producers and public health and the appropriate role of the alcohol industry in alcohol policy space. Design and Methods: Cross‐sectional surveys were conducted in 10 countries as part of the International Alcohol Control study. Alcohol consumption was measured using location‐ and beverage‐specific measures. A level of consumption defined as harmful use of alcohol was chosen and the proportion of the total market consumed in these drinking occasions was calculated for both commercial and informal alcohol. Results: In all countries, sizeable proportions of the alcohol market were consumed during harmful drinking occasions. In general, a higher proportion of alcohol was consumed in harmful drinking occasions by respondents in the middle‐income countries than respondents in the high‐income countries. The proportion of informal alcohol consumed in harmful drinking occasions was lower than commercial alcohol. Discussion and Conclusions: Informal alcohol is less likely to be consumed in harmful drinking occasions compared with commercial alcohol. The proportion of commercial alcohol consumed in harmful drinking occasions in a range of alcohol markets shows the reliance of the transnational alcohol corporations on harmful alcohol use. This reliance underpins industry lobbying against effective policy and support for ineffective approaches. The conflict of interest between the alcohol industry and public health requires their exclusion from the alcohol policy space.